(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the cognitive, didactic, and methodological features of mastering phraseological units (PUs) within the speech practice of undergraduate students at non-linguistic (architectural and civil engineering) universities. The relevance of this research stems from the fact that phraseology represents the most dynamic and semantically opaque layer of vocabulary, causing persistent difficulties for learners during intercultural communication. Based on the authors’ pedagogical experience in Uzbekistan and Azerbaijan, this paper presents a classification of typical speech errors triggered by cross-linguistic interference and literal translation (calquing). As a solution, the authors introduce and validate a methodology of "professionally metaphorical framing," where structural, spatial, and geometric idioms serve as a cognitive bridge to develop natural, idiomatically accurate speech production.